COMPARISON OF MNOTE APPLICATION DEVELOPMENT EFFICIENCY USING LOW CODE AND FULL CODE DEVELOPMENT APPROACHES - Gunadi, Gagah Aji; Kusumo, Dana Sulistyo (Informatika, Universitas Jenderal Soedirman, 2024)
Low Code Development has become more popular in recent years as it offers the ability to develop applications faster. Before the concept of Low Code programming, problems related to the efficiency of application development time were often faced when using manual or Full Code programming approaches. The problem becomes crucial when working on a large-scale application development scope. In this research, the author tries to measure and compare the difference in development efficiency between Low Code and Full Code approaches in the development of a web-based application called MNote, an order recording application for D'Happy food and beverage restaurant in Pemalang, Central Java. The author used OutSystems as the Low Code Platform (LCP) and MongoDB, ExpressJS, ReactJS, NodeJS (MERN) in the Full Code approach. The results showed that the Low Code Development approach takes 51.12% faster than the Full Code Development approach in developing the MNote application. Based on the results of the research, it can be concluded that the use of Low Code Development has a considerable influence in terms of time efficiency and ease of database integration.